Evaluation of Plaque Index, Gingival Index and Oral Health-Related Quality of Life in Obese Patiens - Ayan, Gizem; Dayı, Burak (Odovtos - International Journal of Dental Sciences, 2022)
Obesity is a chronic disease that may be related to caries, periodontitis, xerostomia, and dental erosion, as well as increasing morbidity and mortality. The aim of this study was to evaluate the plaque index (Silness & Löe, 1964), the gingival index (Löe & Silness, 1963), and the oral health-related quality of life (OHRQoL) in obese patients. The study included 45 extremely obese, 45 obese, and 45 normal-weight individuals between the ages of 18 and 58. The plaque index and gingival index of the individuals were determined by clinical examination by probing. In addition, the Oral Health Impact Profile-14 (OHIP-14) questionnaire was used for the OHRQoL. The IBM SPSS Statistic 22.0 software program was used for the statistical evaluation of the study data. The plaque index and gingival index values were statistically higher in obese compared to normal weight individuals (p<0.05). Both plaque index and gingival index values were not statistically significant between the extremely obese and control groups (p>0.05). There was no statistically significant difference between the OHIP-14 total scores of the groups (p>0.05). Increased apparent plaque index and gingival index values in obese patients may adversely affect periodontal health.